PEMBERDAYAAN KADER DALAM PEMANFAATAN RAPOR KEHAMILAN SEBAGAI “SELF ASSESMENT” UNTUK IBU HAMIL - Siska Helina; Juraida Roito Harahap; Septi Indah Permata Sari (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
The Covid pandemic period caused health services to be limited, so WHO recommended online health services and self-assessment of health conditions at home. The aim of this community service is to socialize the Pregnancy “Rapor” Book to Cadres. This Community Service activity was carried out in the Hall of the Umban Sari Public Health Center, Pekanbaru City, for the January-September 2022 period. The participants of this activity were all cadres representing all posyandu in the working area of ​​the Umban Sari Health Center as many as 14 people. The method of activity used in this community service activity is a question and answer lecture, brainstorming, discussion and role playing in filling out the book